The peculiarities of ICT students‘ drop-out because of academic arrears - Saulius Preidys (Computational Science and Techniques, 2015)
Lack of ICT specialists is a big problem in Lithuania for many years. Even ICT specialists are prepared both by universities and colleges, need of those specialists is increasing every year. Students’ enrolment to the ICT related study programmes is increasing a little every year, but only around 51% of them complete their studies. There are very different reasons of students drop-out: health problems, characteristics of personality (lack of responsibility, self-doubts, etc.), socio-economic factors, organisation of study process (Barkauskaitė & Gudžinskienė 2006). In this article a different approach is used to academic arrears – using statistical calculations, academic arrears of students of Vilnius University, Faculty of Mathematics and Informatics from 1991 till 2012 are analysed. At the end of the article, justification of a theoretical model is presented, using which students’ drop-out peculiarities in different study programmes can be observed. DOI: 10.15181/csat.v3i2.1114